KUALITAS PELAYANAN PENGELOLAAN PENGADUAN PELAYANAN PUBLIK LAPOR! OLEH PEMERINTAH KOTA BANJARMASIN - Maulana Achmadi (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
Public Services in Indonesia have received extra attention since the enactment of Law Number 25 of 2009 concerning Public Services (Public Service Law). The issuance of the Public Service Law does not necessarily improve the quality of public services, including in terms of complaint management. This study aims to describe the quality of public service complaints management services LAPOR! by the Banjarmasin City Government, as well as finding the supporting factors and inhibiting factors in the service of managing public service complaints. LAPOR! by the Banjarmasin City Government. The approach used in this study is a qualitative approach that focuses on process analysis of the phenomenon being studied with a descriptive type with data collection techniques through observation and interviews. The results of this study show that all the indicators get a positive response from service users. Only the tangible aspects of the process quality dimension found some important notes to improve. In addition, the leadership factor of the Mayor of Banjarmasin is one of the driving forces in maintaining the quality of complaints management services for public services LAPOR!, this is evidenced by the strengthening of the Standard Operating and Procedures (SOP) LAPOR! through Mayor Regulations as well as reward and punishment mechanisms to agencies based on speed in responding to complaints.